2014
DOI: 10.1007/s10646-014-1261-3
|View full text |Cite
|
Sign up to set email alerts
|

Body size, nuptial pad size and hormone levels: potential non-destructive biomarkers of reproductive health in wild toads (Bufo bufo)

Abstract: Amphibians are declining and fertility/fecundity are major drivers of population stability. The development of non-destructive methods to assess reproductive health are needed as destructive measures are fundamentally at odds with conservation goals for declining species. We investigated the utility of body size, nuptial pad size and forelimb width as non-destructive biomarkers of internal reproductive physiology, by analysing correlations with commonly used destructive methods in adult male toads (Bufo bufo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Amphibians are good bioindicators of environmental pollution (Blaustein and Johnson, 2003); thus, digit ratio may vary among populations due to different hormonal conditions (Manning et al, 2014;Orton et al, 2014). Therefore, in future studies on digit ratio in amphibians, samples of a single species from different populations should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians are good bioindicators of environmental pollution (Blaustein and Johnson, 2003); thus, digit ratio may vary among populations due to different hormonal conditions (Manning et al, 2014;Orton et al, 2014). Therefore, in future studies on digit ratio in amphibians, samples of a single species from different populations should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…; Orton et al. ), and was among the first amphibians for which adverse genetic effects of habitat fragmentation have been demonstrated (Hitchings and Beebee ). Possibly due to life history traits such as skewed sex ratios and high fecundity, B. bufo populations are also often characterized by low amounts of genetic variation and low effective population sizes, combined with a spatial differentiation which exceeds other co‐occurring anurans (Scribner et al.…”
Section: Introductionmentioning
confidence: 99%
“…1) has a large distribution across central eastern and northern Europe (note that the taxonomy of B. bufo has recently been revised: Recuero et al 2012;Arntzen et al 2013Arntzen et al , 2014. Bufo bufo is characterized by a regular occurrence at sites highly impacted by humans (despite measurable physiological consequences: Reading 2007;Janin et al 2011;Orton et al 2014), and was among the first amphibians for which adverse genetic effects of habitat fragmentation have been demonstrated (Hitchings and Beebee 1998). Possibly due to life history traits such as skewed sex ratios and high fecundity, B. bufo populations are also often characterized by low amounts of genetic variation and low effective population sizes, combined with a spatial differentiation which exceeds other co-occurring anurans (Scribner et al 1997;Sepp€ a and Laurila 1999;Brede and Beebee 2004;Flavenot et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this kind of survey is not as frequent as research on tadpoles or laboratory research. Considering that over 30 % of amphibian species are threatened with extinction, the attention of researchers is being directed toward non-invasive methods (Simon et al 2009, 2012; Orton et al 2014). The road mortality of vertebrates offers great opportunities for obtaining material for further research (D’Amico et al 2015; Santos et al 2015), including studies on bioindication (Simon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, including Poland, one of the most widespread species, but also one of the most vulnerable to road mortality, is the common toad Bufo bufo (Głowaciński and Rafiński 2003; Elzanowski et al 2009; Temple and Cox 2009) . Moreover, this species is used with increasingly frequency in attempts to assess the state of environmental pollution (Orton and Routledge 2011; Dobrovoljc et al 2012; Simon et al 2012; Orton et al 2014; Dmowski et al 2015; Pickford et al 2015). Research in urban areas has shown that the number of sites occupied by amphibians, including common toads, has decreased slightly (Budzik et al 2013; Kaczmarek et al 2015).…”
Section: Introductionmentioning
confidence: 99%